Development of a maintenance free tropicalized lead acid battery enhanced by membrane technology - Khoo, T. C. (2004)
The objective of this study is carried out to develop a Maintenance Free Tropicalized Lead Acid Battery enhanced by membrane technology, to overcome problems such as lost of electrolyte, spilt of battery acid onto the battery compartment, and other associated enviamential problems. Asymmetric gas separation membranes were fabricated using polysulfone polymer and solvent. Polymer and solvent concentration were varied with the range of 9.5% to 30% and 90.5% to 70% respectively. The produced membranes were then incorporated into the Lead Acid Battery vent holes that have been designed in this study. Results showed that when the battery was charged at 13.2V (2.2V per cell) over period of 168 hours at 26oC ± 2oC the electrolyte losses is indistinctive, but with charging rate at 14.4V (used by Proton Car) the loss of electrolyte is fall below permitable level with the same parameter. Heat simulation test was concurrently carried out at temperature of 26oC ± 2oC over period of 168 hours without charging, the electrolyte loss was undistinguished but when the battery was simulated under hot bath condition at 82oC ± 2oC the loss is 1.6kg over the initial weight of 12.8kg.